ENGAGEMENT IN LEARNING AS MEDIATOR BETWEEN MOTIVATIONAL BELIEFS AND SCHOOL ACHIEVEMENT: A PATH ANALYSIS - VIOREL-BENIAMIN MIH; CODRUȚA-ALINA MIH (Studia Universitatis Babes-Bolyai, 2020)
ABSTRACT. This study applied the Expectancy-Value Theory to explore the directionality of the associations among academic self-efficacy, motivational beliefs (e.g., expectation of success, task value), procrastination, and engagement in learning as well as the impact of these constructs on educational attainment. The data analysis was done by using structural equation modeling. The results reveal important associations among students' personal variables. Correlational and path analyses show that: (a) self-efficacy is consistently found to predict both expectation of success, task value and procrastination, (b) the associations between self-efficacy and engagement are mediated by motivational beliefs and procrastination, (c) different faceted of engagement (class participation, homework completion, absenteeism) in high school predict educational attainment, and (d) class participation had stronger effects on educational attainment than homework completion. The data analysis provided empirical evidence to better understand the mechanism that mediates self-efficacy and school achievement. Also, the study provides empirical evidence supporting the multifaceted nature of school engagement and demonstrates its utility relative to educational success. The implications of these findings for teaching and learning a specific subject matter in formal classroom contexts are discussed.